Impact of prophylactic corticosteroids on systemic inflammation after extensive atrial ablation in pigs - Nascimento, Thais [UNIFESP] (2012)
Aims Prophylactic corticosteroids have been reported to attenuate the increase in C-reactive protein (CRP) and the incidence of atrial fibrillation (AF) both after heart surgery and AF ablation. We tested the impact of a single prophylactic corticosteroid dose on ultrasensitive CRP 24 h and 14 days after extensive linear atrial ablation (8 mm or 3.5 irrigated tip) guided by electroanatomical mapping (NavX) in pigs with normal hearts.Methods and results Pigs (n = 19; 35 kg) were divided into three groups: corticoid (n = 7), atrial ablation with administration of 500 mg methylprednisolone intravenous at anaesthetic induction; control (n = 7), atrial ablation only; and sham (n = 5), surgical procedure without ablation. Troponin and CRP were measured before, 24 h and 14 days after the procedure. After sacrifice, lesions were analysed macroscopically and histologically. Linear lesions were created in the right (n = 23) and left (n = 21) atrium of 14 animals, with no difference between groups. in all groups there was elevation of troponin and CRP 24 h after ablation, with a return to baseline values after 14 days. However, CRP levels of the control, corticoid, and sham groups were similar at all three time points analysed (baseline P = 0.52, 24 h P = 0.21, 14 days P = 0.66). Histological analysis did not show any difference between corticoid and control groups.Conclusion in this model, extensive biatrial RF ablation, per se, does not promote systemic inflammation. the use of a prophylactic single corticoid dose before ablation did not prevent systemic inflammation or alter the healing of the lesions.